This preview shows page 1. Sign up to view the full content.
Unformatted text preview: ² , which is the form we want. In the same way one sees, f ( e 2 ) = 1 1 + s 2 ± 2 s s 21 ² , and hence, from ( ** ), A f = 1 1 + s 2 ± 1s 2 2 s 2 s s 21 ² . It is much simpler to ﬁnd A g , since clearly g ( e 1 ) = e 1 and g ( e 2 ) =e 2 , and so A g = ± 11 ² . Hence, from ( * ), A g ◦ f = A g A f = 1 1 + s 2 ± 11 ²± 1s 2 2 s 2 s s 21 ² = 1 1 + s 2 ± 1s 2 2 s2 s 1s 2 ² . 21 /september/ 2005; 22:09 12...
View
Full
Document
This note was uploaded on 10/03/2010 for the course MATH 380 taught by Professor Gladue during the Fall '08 term at Roger Williams.
 Fall '08
 Gladue
 Calculus, Formulas

Click to edit the document details